2008
DOI: 10.4049/jimmunol.180.4.2641
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 Mediates Region-Specific Antiviral T Cell Trafficking within the Central Nervous System during West Nile Virus Encephalitis

Abstract: Regional differences in inflammation during viral infections of the CNS suggest viruses differentially induce patterns of chemoattractant expression, depending on their cellular targets. Previous studies have shown that expression of the chemokine CXCL10 by West Nile virus (WNV)-infected neurons is essential for the recruitment of CD8 T cells for the purpose of viral clearance within the CNS. In the current study we used mice deficient for the CXCL10 receptor, CXCR3, to evaluate its role in leukocyte-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(160 citation statements)
references
References 77 publications
8
151
1
Order By: Relevance
“…Using genetically deficient mice and antibody neutralization approaches, Klein and colleagues showed that CXCL10 is critical for the recruitment of CXCR3-expressing T cells into the CNS and survival from WNV infection in mice [25]. Likewise, genetic deficiency of CXCR3 recapitulated this phenotype [50,51]. Loss of either resulted in decreased T-cell recruitment to the CNS and increased viral burden and mortality.…”
Section: Cxcr3/cxcl10mentioning
confidence: 99%
“…Using genetically deficient mice and antibody neutralization approaches, Klein and colleagues showed that CXCL10 is critical for the recruitment of CXCR3-expressing T cells into the CNS and survival from WNV infection in mice [25]. Likewise, genetic deficiency of CXCR3 recapitulated this phenotype [50,51]. Loss of either resulted in decreased T-cell recruitment to the CNS and increased viral burden and mortality.…”
Section: Cxcr3/cxcl10mentioning
confidence: 99%
“…While these chemokines are not detectable in the healthy brain, their expression is highly upregulated following infection of the CNS with various viruses (2,3,10,21,23,24). Deficiency of CXCR3 has been associated with reduced trafficking to and/or positioning of T cells in the CNS in a number of different virally-induced disease models, such as West Nile virus encephalitis (45), mouse hepatitis virus encephalitis (43), and dengue virus encephalitis (18).…”
Section: Ymphocytic Choriomeningitis Virus (Lcmv) Is a Membermentioning
confidence: 99%
“…Elimination of virus-infected cells in the CNS requires a CD8 T-cell response [233][234][235][236]. In response to WNVand JEV infections, neurons release CXCL10, which is required for recruitment of CD8 T cells into the brain via the C-X-C chemokine receptor (CXCR)3 [151,170].…”
Section: Viral Clearance From the Cnsmentioning
confidence: 99%